Applying computational protein design to therapeutic antibody discovery - current state and perspectives - Bielska, Weronika; Jaszczyszyn, Igor; Dudzic, Pawel; Janusz, Bartosz; Chomicz, Dawid; Wrobel, Sonia; Greiff, Victor; Feehan, Ryan; Adolf-Bryfogle, Jared; Krawczyk, Konrad (Frontiers in Immunology, 2025)
Machine learning applications in protein sciences have ushered in a new era for designing molecules in silico. Antibodies, which currently form the largest group of biologics in clinical use, stand to benefit greatly from this shift. Despite the proliferation of these protein design tools, their direct application to antibodies is often limited by the unique structural biology of these molecules. We note that multiple methods attempting antibody design focus on the discovery of an antigen-specific antibody. Here, we review the current computational methods for antibody design, focusing on binder discovery, contextualizing their role in the drug discovery process.